Intensive Care Management of Eclampsia with HELLP Syndrome: A Case Report - Liliriawati Ananta Kahar; Wiwi Monika Sari; Mentari Faisal Putri (HM Publisher, 2023)
Background: The incidence of HELLP syndrome is approximately 0.1-1% of all pregnant women and 5.5% of patients admitted to the ICU. Hemolysis, elevated liver enzymes, and thrombocytopenia are the characteristics of HELLP syndrome. Case Presentation: A 38-year-old patient with diagnosed G4P3A0L3 31-32 weeks of preterm pregnancy + eclampsia on MgSO4 regimen, HELLP syndrome + twice previous Sectio cesarean + breech presentation. On physical examination, the general condition was blood pressure 199/103 mmHg. The results of laboratory tests post-op were hemoglobin 7,1 g/dL, leukocytes 15.930, hematocrit 24%, and platelets 38,000. The results of other laboratory tests showed decreased albumin levels (Alb 2,4), increased levels of total bilirubin 14,7, direct bilirubin 10,8 and indirect bilirubin 3,9, increased liver enzyme SGOT 2001 SGPT 513. Conclusion: HELLP syndrome is a threatening clinical problem. Appropriate and adequate management, especially in the Intensive care unit, is needed to prevent severe complications to reduce morbidity and mortality rates in patients with HELLP syndrome.